JCU 2017 Reviewers (Journal of Clinical Ultrasound, 2018)
We report the case of a 38-year-old recreational female runner with anterior and lateral chronic exertional compartment syndrome treated with ultrasound-guided fasciotomy using a V-shaped meniscotome. She began her return-to-run protocol 8 days postprocedure and achieved full symptom resolution. At 6 months, ultrasound revealed persistent fascial separation without complications, representing the first report of long-term sonographic outcomes following fasciotomy for chronic exertional compartment syndrome. These findings support further prospective studies to evaluate the clinical and sonographic outcomes of this technique.